2002
DOI: 10.1046/j.1468-2982.2002.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Meningeal Blood Flow by Nitric Oxide - Interaction with Calcitonin Gene-Related Peptide Receptor and Prostaglandin Synthesis Inhibition

Abstract: This study addresses possible interactions of the vasodilators nitric oxide (NO), calcitonin gene-related peptide (CGRP) and prostaglandins, which may be implicated in the generation of vascular headaches. Local application of the NO donator diethylamine-NONOate (NONOate) to the exposed dura mater encephali of the rat caused dose-dependent increases in meningeal blood flow recorded by laser Doppler flowmetry. Pre-application of the CGRP receptor antagonist CGRP8-37 significantly attenuated the evoked blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
2
20
0
1
Order By: Relevance
“…The increase in NO may not only serve as a countermeasure to effect cerebral vasodilatation to preserve oxidative metabolism in the face of prevailing hypoxemia but may have also stimulated focal CGRP synthesis and release resulting in neurogenic vasodilatation, inflammation, hyperalgesia, and allodynia. 20 Alternatively, the blood-brain barrier, which we have shown to remain mostly intact during hypoxia, 13 may have also prevented intrathecally formed CGRP from entering the extracranial circulation in sufficient amounts to permit molecular detection.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in NO may not only serve as a countermeasure to effect cerebral vasodilatation to preserve oxidative metabolism in the face of prevailing hypoxemia but may have also stimulated focal CGRP synthesis and release resulting in neurogenic vasodilatation, inflammation, hyperalgesia, and allodynia. 20 Alternatively, the blood-brain barrier, which we have shown to remain mostly intact during hypoxia, 13 may have also prevented intrathecally formed CGRP from entering the extracranial circulation in sufficient amounts to permit molecular detection.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation of the smooth muscle cell and thereby vasodilation is finally caused by the decrease of Ca 2+ [25]. However, additional mechanisms that include a coupling of NO and CGRP release have been discussed [8, 18, 26, 27]. Great interest lies on the involvement of NO induced mechanisms within the trigeminal pathway since it is known that NO can induce headache with the clinical phenotype of migraine [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed NO generation is involved in the cranial parasympathic loop [34] that is active in trigeminal autonomic cephalalgias (TACs) [35]. In a study monitoring the meningeal blood flow during local application of vasodilators as well as potential antagonists it was concluded that NO dependent blood flow release is independent of the release of prostaglandins, a product of cyclooxygenases, but is co-induced by a NO triggered CGRP release [27]. The model used did not reflect trigeminal activation itself, and only local effects were monitored.…”
Section: Discussionmentioning
confidence: 99%
“…NO is involved in the maintenance of the basal level of dural arterial blood flow as well as in the electrically evoked flow increases mediated by CGRP released from dural afferent fibers. The synergistic effect of NO and CGRP on the stimulated blood flow was postulated to be due in part to a NO-mediated facilitation of the CGRP release [Messlinger et al, 2000], while prostaglandins are not significantly involved [Strecker et al, 2002]. CGRP synthesis and release are coordinately stimulated by the vasodilator NO, a signaling mechanism that occurs within the trigeminal ganglia neurons.…”
Section: Cgrp Sp and Nka Involvement In Migrainementioning
confidence: 99%